Thermodynamic Properties of γ- and δ-Lactones: Exploring Alkyl Chain Length Effect and Ring-Opening Reactions for Green Chemistry Applications - Ana L. R. Silva; Gastón P. León; Vladimír Lukeš; Erik Klein; Maria D. M. C. Ribeiro da Silva (Molecules)
An extensive thermochemical study of γ-undecanolactone and δ-undecanolactone has been developed using two complementary calorimetric techniques. The combustion energy of each compound was determined by static-bomb combustion calorimetry, and the corresponding enthalpy of vaporization was determined by high-temperature Calvet microcalorimetry, in which both properties of each compound are reported at T = 298.15 K. The standard molar enthalpy of formation in the gas phase of each lactone was derived by the combination of the experimental results. Additionally, high-level computational calculations were carried out, using composite ab initio G4 and G4(MP2) methods, as well as DFT M06-2X/6-311++G(d,p) approach, to estimate the corresponding enthalpy of formation in the gas phase. The experimental and computational results are in good agreement. The G4 and G4(MP2) methods show the best accordance with experimentally determined gas phase enthalpies of formation. The experimental results are discussed in terms of structural contributions to the energetic properties of the lactones studied, as well as to other alkylated γ- and δ-lactones, and empirical correlations are suggested for the estimation of the standard molar enthalpies of formation, at T = 298.15 K, for other alkylated γ- and δ-lactones, both in the liquid and gaseous phases, as well as for the respective enthalpies of vaporization. Finally, the thermochemistry of individual steps of lactone ring opening and successive decarboxylation mechanism, including the identification of transition states, was studied using the M06-2X/6-311++G(d,p) approach.